Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 2401 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Cynomys ludovicianus (Ord, 1815)", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 2401 records from 50 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0085610-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences